Inflammation and serotonin deficiency in major depressive disorder: molecular docking of antidepressant and anti-inflammatory drugs to tryptophan and indoleamine 2, 3-dioxygenases. Issue 5 (27th May 2022) - Dawood, Shazia; Bano, Samina; Badawy, Abdulla A.-B.
Abstract: The roles of the kynurenine pathway (KP) of tryptophan (Trp) degradation in serotonin deficiency in major depressive disorder (MDD) and the associated inflammatory state are considered in the present study. Using molecular docking in silico, we demonstrate binding of antidepressants to the crystal structure of tryptophan 2, 3-dioxygenase (TDO) but not to indoleamine 2, 3-dioxygenase (IDO). TDO is inhibited by a wide range of antidepressant drugs. The rapidly acting antidepressant ketamine does not dock to either enzyme but may act by inhibiting kynurenine monooxygenase thereby antagonising glutamatergic activation to normalise serotonin function. Antidepressants with anti-inflammatory properties are unlikely to act by direct inhibition of IDO but may inhibit IDO induction by lowering levels of proinflammatory cytokines in immune-activated patients. Of six anti-inflammatory drugs tested, only salicylate docks strongly to TDO and apart from celecoxib, the other five dock to IDO. TDO inhibition remains the major common property of antidepressants and TDO induction the most likely mechanism of defective serotonin synthesis in MDD. TDO inhibition and increased free Trp availability by salicylate may underpin the antidepressant effect of aspirin and distinguish it from other nonsteroidal anti-inflammatory drugs. The controversial findings with IDO in MDD patients with an inflammatory state can be explained by IDO induction being overridden by changes in subsequent KP enzymes influencing glutamatergic function. The pathophysiology of MDD may be underpinned by the interaction of serotonergic and glutamatergic activities.